Karakteristik Dan Makna Dari Mitoni Desa Kaligangsa Kulon Brebes, Jawa Tengah - Damayanti, Welsi; Khoerunisa, Sabilla (Universitas PGRI Semarang, 2025)
The issue discussed in this research is the characteristics and meaning of the mitoni of Kaligangsa Kulon Brebes Village, Central Java. This research aims to reveal the characteristics of the Mitoni tradition found in Central Java as a type of oral literature. The characteristics of the mitoni tradition in Central Java can be described and analyzed through Ruth Finnegan's theory which relates to the components of an oral literary tradition. This study is expected and aimed at being able to create cultural characteristics and revive the Mitoni tradition which may now be alienated due to the influence or impact of globalization and modernization. The things studied in this research are the components of the mitoni tradition, which are: speakers, props, participants and prayer readings. The method used in this research is descriptive qualitative. Data collection carried out in this research was interviews.